DAMPAK EKONOMI KELUARGA DI WILAYAH TERPENCIL TERHADAP PENDIDIKAN ANAK DALAM ERA DIGITAL - Indri Yanti, Revina; Noverita, Anisa (Prodi Pendidikan IPS STKIP AL MAKSUM, 2025)
The family economy is a combination of income and social status of parents; The higher the social status, the greater the funds allocated for children's education costs. By considering children's research in the digital era, this study aims to examine the family economy in rural areas. This research combines the methodology of literature study with a qualitative approach. The findings of the study show that, especially in the digital era, family economic conditions have a significant impact on children's education. Education in remote areas often faces significant constraints, including uneven distribution of teachers, poor infrastructure, and limited access to high-quality learning resources. Children's education in the digital era is greatly influenced by their family's financial condition. Today's children need educational opportunities, and as technology evolves, they also need access to gadgets and the internet. Education in Indonesia has changed dramatically due to the rapid advancement of digital technology. The digitalization era has shifted the learning paradigm from traditional to a system that is much more interactive, easily accessible, and can adapt to the needs of the digital generation.